A pilot investigation validating the antecedents measured by the classroom engagement instrument in Chinese educational settings - Zhiyuan Yang; Connie Shin @ Connie Cassy Ompok; Ting Pick Dew; Sabariah Bte Sharif (Journal of Computational Analysis and Applications, 2024)
The current research endeavors to substantiate the preconditions of classroom engagement instruments by employing rigorous scale validation methodologies. A tailored questionnaire comprising 78 items was distributed to 215 undergraduate students in China, undergoing Confirmatory Factor Analysis (CFA). The findings reveal that the influencing factors of classroom engagement, encompassing teacher-student interactions, peer relationships, and learning motivation, exhibit strong reliability and validity. This validated 78-item scale serves as a viable instrument for assessing classroom engagement, enhancing our understanding of the underlying factors that influence classroom engagement. Furthermore, the discussion delves into both the practical implications and methodological considerations of this research.